INTENSITAS ASUPAN GIZI DALAM MENGEMBANGKAN KESEHATAN ANAK USIA 5-6 TAHUN DI TK UMMI ERNI DESA PEMATANG JOHAR - Reka Indriani; Mesiono Mesiono; Sapri Sapri (JURNAL RAUDHAH, 2019)
When children are in a process of growth and rapid development, parents and young people should pay atantion to the health and health of children so that the children can grow and develop according to their age.The purpose of this research is to identify: (1). The children nutrition 5-6 years old, (2). The children health development 5-6 years old, (3). The alternative to protect children health. This research is a quantitative descriptive research. The participants of this research which are include the principal, teacher, and the student parents at class B who is 5-6 years old. In process of collecting the data the researcher used interview method, observation, and documentation. From the research we can conclude 1).Nutrition or food that often given to the children is just four healthy five perfect foods, 2).The children in TK Ummi are the children who have healtiness, 3). The alternative that can be commited to protect the children health is do the practice, make the children common to throw the rubbish in the right place,  check the children nail, stock the pure water, set many dustbins and make a common to wash their hand before eating.